Reproductive biology of the neotropical superfetaceous Pamphorichthys hollandi (Cyprinodontiformes: Poeciliidae) - Casatti, Lilian [UNESP]; Carvalho, Fernando R. [UNESP]; Veronezi Jr., José L. [UNESP]; Lacerda, Daniel R. [UNESP] (My University, 2006)
We investigated sex ratio, reproductive period, fecundity, and sexual dimorphism of Pamphorichthys hollandi in southeastern Brazil. Reproductive status was identified according to a female's gonads/embryos development scale. Of the 613 collected specimens, 373 (60%) were females and 240 (40%) males giving a sex ratio of 1 male:1.6 female. Sexual dimorphism was evident in respect to body size, body coloration, and anal and pelvic-fin morphologies. The highest proportion of reproductive females was registered in January and February, which represent wet and hot periods. The simultaneous presence of more than one litter at different stages of development within a single female characterized this species as superfetaceous. © 2006 by Verlag Dr. Friedrich Pfeil.